1991
DOI: 10.1002/pola.1991.080290408
|View full text |Cite
|
Sign up to set email alerts
|

Studies of particle formation in styrene emulsion polymerizations using 9‐vinyl anthracene as a probe molecule

Abstract: The effects of 9‐vinyl anthracene (VAn) on solution and emulsion polymerization of styrene are examined, to gain information about the mechanism of particle formation in emulsion polymerizations. Styrene solution polymerization in ethyl benzene is found to be inhibited by small amounts of VAn. In an emulsion system, the effects of VAn are found to depend on surfactant concentration [S]. With [S] = 0, addition of VAn engenders some inhibition and very little change in the steady‐state polymerization rate. As [S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1991
1991
2006
2006

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…The main conclusion which might be drawn from our analysis is that, at least for styrene emulsion polymerization with surfactant concentrations well above CMC, early-time PSDs, when properly analyzed, are in agreement with the formation rate of latex particles being monotonically decreasing (rather than increasing) for much of the nucleation time. Recently, some new experimental data on styrene polymerization became available supporting the hypothesis that, above CMC, micellar entry can significantly contribute to particle formation mechanism (Pearson et al, 1991). Basically, these results agree with the interpretation of the PSD data given here.…”
Section: Comparison With Experimental Datasupporting
confidence: 90%
“…The main conclusion which might be drawn from our analysis is that, at least for styrene emulsion polymerization with surfactant concentrations well above CMC, early-time PSDs, when properly analyzed, are in agreement with the formation rate of latex particles being monotonically decreasing (rather than increasing) for much of the nucleation time. Recently, some new experimental data on styrene polymerization became available supporting the hypothesis that, above CMC, micellar entry can significantly contribute to particle formation mechanism (Pearson et al, 1991). Basically, these results agree with the interpretation of the PSD data given here.…”
Section: Comparison With Experimental Datasupporting
confidence: 90%
“…It has been reported that a coagulation/homogeneous nucleation mechanism dominated particle formation in the batch polymerization of styrene below the CMC. 24 Water soluble oligomers were reported in the polymerization and copolymerization of styrene. 19,25 If coagulation occurred near the beginning of polymerization to produce a constant number of growing particles, this results in monodispersity.…”
Section: Mechanism Of Particle Growthmentioning
confidence: 99%
“…14 The molecular weight and high hydrophobicity of STPO promote the formation of rigid surface film 35 and suppress Ostwald ripening. 15 In the former case, the transfer of hydrophobic components (initiator or its radicals) from monomer droplets to droplets or polymer particles within the droplets or particles clusters through the interface between droplets during collision is reduced and the release of primary radicals is depressed. In the latter case, the depressed monomer droplet degradation depresses the transfer of monomer and hydrophobe(STPO) to the reaction loci.…”
Section: Polymerization Ratementioning
confidence: 99%